2018
DOI: 10.1007/s10787-018-0503-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of isoliquiritigenin against cerebral injury in septic mice via attenuation of NF-κB

Abstract: These results demonstrate that ISL causes protection of CLP-induced sepsis in experimental mice via multiple pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Further, ISL maintained antioxidant enzyme expression during LPS-induced neuroinflammation. Consistent with these findings, ISL also restored the oxidant–antioxidant balance in rodent models of brain injury induced by cocaine [27], sepsis [28], ICH [11], and middle cerebral artery occlusion [29]. Oxidative stress is a key contributor to neuronal injury and death, and cognitive capacity is reduced by neuronal cell loss.…”
Section: Discussionmentioning
confidence: 63%
“…Further, ISL maintained antioxidant enzyme expression during LPS-induced neuroinflammation. Consistent with these findings, ISL also restored the oxidant–antioxidant balance in rodent models of brain injury induced by cocaine [27], sepsis [28], ICH [11], and middle cerebral artery occlusion [29]. Oxidative stress is a key contributor to neuronal injury and death, and cognitive capacity is reduced by neuronal cell loss.…”
Section: Discussionmentioning
confidence: 63%
“…Other studies have shown that ISL can reduce the expression of COX-2 and iNOS in septic mice [ 11 ] and HT-29 cells [ 22 ]. COX-2 is an inducible enzyme activated by cytokines and growth factors, such as IL-1 and IL-6, while iNOS is a nitric oxide synthetase activated by pathologic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…A flavonoid with a chalcone structure, ISL, readily passes through the blood-brain barrier to exert its central actions [31]. Peripherally injected ISL is metabolized to liquiritigenin Evidence-Based Complementary and Alternative Medicine (another important bioactive flavonoid in G. radix) and other glucuronidated metabolites via cytochrome P450 2C19 and UDP-glucuronosyltransferases in the liver [32,33].…”
Section: Discussionmentioning
confidence: 99%